Analisis Penerapan Standart Akuntansi Pemerintah di Kantor Camat Sei Balai - Sri Wulandari; Aqwa Naser Daulay (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
After Government Regulation (PP) No.71 of 2010 concerning Government Accounting Standards (SAP) and Minister of Home Affairs Regulation (Permendagri) No.64 of 2013 were issued, Article 10 paragraph (2) states that every regional government is obliged to provide accurate financial reports and accurate according to the provisions in effect starting in the 2015 fiscal year, if they use accrual-based SAP. The purpose of this research is to find out how the presentation of financial reports is carried out and how ready the district government is. Sei Balai to present accrual-based SAP financial reports. Data was collected through field studies and analyzed using descriptive methods. Data was collected through field research. The research results show that the government of Kec. Sei Balai has not implemented the PP. No.71 of 2010, but is in accordance with PP. No.24 of 2005, which means using the cash basis for accruals. Apart from that, there are obstacles in preparation because it requires an increase in the number and quality of implementing human resources with appropriate accounting education, socialization, and technical guidance to produce reliable and transparent financial reports. There is a shortage of implementing human resources in each SKPD and supporting equipment is not yet ready.